HUMAN IMMUNODEFICIENCY VIRUS-HEPATITIS C VIRUS COINFECTION: A REVIEW ON NECESSITY OF DIETARY COMPOUNDS FOR ANTIRETROVIRAL THERAPY - Selvaraj, Suganya; Piramanayagam, Shanmughavel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Human immunodeficiency virus (HIV)-hepatitis C virus (HCV) coinfection is a major health problem around worldwide. One-third of the HIV-infected patients suffer from chronic hepatitis (HCV). The risk factors of coinfected patients are very high while compared to the monoinfected patients; they are having higher HCV viral load is associated with a severe liver damage. The use of highly active antiretroviral therapy (HAART) dramatically increases the survival of HIV/HCV-coinfected patients by preventing the depletion of CD4 cell counts and delaying the progression of fibrosis which reduces the complications related to end-stage liver damage. Reverse-transcriptase inhibitors and protease inhibitors are very commonly used drugs for the treatment of coinfection. Combination drugs and synthetic drugs are playing a pivotal role in the coinfection therapy. Under HAART, the coinfected patients are affected by many adverse effects such as mitochondrial toxicity, hypersensitivity, and lipodystrophy syndrome. However, the adverse effects of most herbal drugs are relatively less frequent when the drugs are used properly compared with synthetic drugs; it may help to protect the patients from severe adverse effects. This review collates to the importance of plant-derived drugs for the treatment of HIV-HCV coinfection.